Pengembangan Multimedia Interaktif Berbasis Android Pada Materi Elastisitas Bahan untuk SMA Kelas XI - Rosana Yulia; Ernita Susanti; Rahmat Rizal (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The development of the use of Android opens up opportunities for the use of Android in supporting learning. For example, the use of Android as an interactive learning medium. This study aims to determine and understand the development of android-based interactive multimedia in physics subjects with elasticity material for class XI SMA using a 4-D model. However, it is focused on testing the validity of Android-based interactive multimedia on the content and display aspects. The sample that became the subject of this study was students of class XI SMAN 6 Tasikmalaya. Meanwhile, the instrument used to collect data in this study was a questionnaire analysis of student needs for learning media and product validity testing. Validity uses a Likert scale with an assessment score on the content and appearance aspects validity sheet. The results show that the media developed is valid. With the results of the validity test on the content aspect, namely 0.87. Meanwhile, the results of the validity test on the content aspect are 0.93, so the average is 0.9, which means it is included in the valid category. As a result, this Android-based interactive multimedia can be used in class XI high school physics learning activities with material elasticity.